The Effect of Think-Pair-Share Strategy on Student Learning Achievement: English - Akhmad Nuris Hidayat Nuris (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Think Pair Share was one of the learning models that give students the opportunity to work alone as well as work together. The researcher used a Think-Pair-Share Strategy in the learning process to know the effectiveness of student learning achievement. It used a quantitative method and took 50 students as a sample and used a questionnaire. Then the data was analyzed using the product moment formula.The r of the calculation result is greater than the r of the table, both at the level of significance of 5% and 1%. Thus, the alternative hypothesis (Ha) is accepted, namely the existence of a positive influence between the variables X and Y, while the null hypothesis (Ho) is rejected. So there is an influence between the think pair share learning model on student achievement